2008
DOI: 10.2190/pm.38.3.c
|View full text |Cite
|
Sign up to set email alerts
|

Mass Murders: Implications for Mental Health Professionals

Abstract: In this article, we attempt to uncover whether mass murders (the killing of multiple victims in single events) are preventable acts, the extent to which they are contributed to by biological and psychological factors, the notion that they are inextricably linked to mental illness, the role of the media, and what lessons can be learned by mental health professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 9 publications
2
42
0
2
Order By: Relevance
“…These findings are supported by Aitken et al's (2008) research that showed 14 of the deadliest school attacks occurred in the last 8 years and span 8 different countries (i.e., 6 in the U.S., 2 in China, and 1 each in Canada, Britain, Japan, Yemen, Germany, and Finland-p. 265). In addition, Hempel et al (1999) identified 30 mass murders in the United States and Canada from 1949 to 1998 and found that the majority of them (21 out of 30) occurred after 1985.…”
Section: Prevalence Of Mass Murdersupporting
confidence: 61%
See 3 more Smart Citations
“…These findings are supported by Aitken et al's (2008) research that showed 14 of the deadliest school attacks occurred in the last 8 years and span 8 different countries (i.e., 6 in the U.S., 2 in China, and 1 each in Canada, Britain, Japan, Yemen, Germany, and Finland-p. 265). In addition, Hempel et al (1999) identified 30 mass murders in the United States and Canada from 1949 to 1998 and found that the majority of them (21 out of 30) occurred after 1985.…”
Section: Prevalence Of Mass Murdersupporting
confidence: 61%
“…Holmes and Holmes (1998) suggested that when creating a definition of mass murder, one needs to take into consideration the number of victims slain, the location of the murders, and timing of the killings. Mass murder is generally limited to incidents that took place within a 24-hour period, or single event (Aitken et al 2008;Dietz 1986;Duwe 2004;Duwe 2005). Although mass murders usually occur at one time, one also finds incidents that occur at different times, minutes or hours apart, and in different locations, as in a few blocks away, which would still fall under the mass murder umbrella (Holmes and Holmes 1998).…”
Section: Mass Murder Definitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, blocked goal achievement (e.g., being expelled from school or fired from work) and second, negative social interactions (e.g., bullying by fellow students) (Ames, 2005;Duncan, 1995;Duwe, 2007;Fox & Levin, 1994;Langman, 2009;Lankford & Hakim, 2011;Levin & Madfis, 2009;Lieberman, 2006;Newman & Fox, 2009;Newman et al, 2004;O'Toole, 2000;Rugala, 2003;Vossekuil et al, 2002). Mass shooters typically isolate themselves socially, cutting themselves off from emotional support and have relatively little or no close relationships or intimate contact with others (Fox & Levin, 2003;Hempel & Richards, 1999;Aitken, Oosthuizen, Emsley, & Seedat, 2008;Mullen, 2004;Levin & Madfis, 2009;Bowers, Holmes, & Rhom, 2010). Mass shooters are frequently single or divorced (Hempel & Richards, 1999), with no family or friends that can influence their behavior in a positive way (Levin & Madfis, 2009;Bowers et al, 2010).…”
Section: Mass Shooters and Mental Illnessmentioning
confidence: 99%